Understanding University Teachers’ Perspectives of English Medium Instruction in Indonesia - Santoso , Wulandari; Rindu Kinasih , Putri (Elsya : Journal of English Language Studies, 2022)
Despite the massive growth of universities offering EMI in non-Anglophone countries including Indonesia, there is little research regarding the underlying rationales for the implementation of EMI and the perceptions of lecturers in relation to the enactment of EMI. Several studies have also highlighted the absence of official guidelines for EMI in this context, which has contributed to the dissimilar practices of EMI among Indonesian universities. This case study aimed to find out the underpinning rationales for the implementation of EMI at the Indonesian universities. It also aimed to investigate how lecturers at the Indonesian universities perceived the implementation of EMI. Semi-structured interviews were conducted with nine non-English lecturers from both state and private Indonesian universities. The results of this study showed that some factors, including promoting university internationalisation, enhancing academic reputations, and taking part in international competitions, were found to underpin the implementation of EMI. In addition, this study also underlined the issue of internationalisation in relation to Englishisation and its impacts on EMI. In this study, the participants' use of the Indonesian language intended to facilitate communication and understanding of content learning could also be seen as a way to value multilingual practices. Therefore, this study suggests that the Indonesian linguistic ecology where Bahasa Indonesia and English co-exist with the hundreds of local languages should be taken into consideration in the educational language policy-making.